Stitching the Threads of Handbags : An Insight into Customers’ Attitude Toward Counterfeit Handbag Purchase - Kaur, Jasmandeep; Yadav, Renu; Yadav, Dhanjay (Prabandhan: Indian Journal of Management, 2025)
Purpose : To explore what motivated the customer to buy a counterfeit handbag and how the attitude of the customer led to a willingness to purchase counterfeit handbags. Methodology : SPSS (24) was used to conduct the exploratory factor analysis (EFA). This was followed by confirmatory factor analysis (CFA) for further validation, and finally, path analysis was conducted using AMOS (20). Data was obtained from 582 respondents. Findings : Four factors or statuses (Customers seeking novelty, customers seeking status, customers with a sense of integrity, and customers who perceived risks) were identified as influencing customers’ attitudes toward counterfeit handbags. This research offered insights into these factors by dividing the analysis into two parts. In the first part, factors influencing customers’ attitudes toward counterfeit products (positively or negatively) were analyzed. The next step tested whether that attitude led to a willingness to buy counterfeit handbags. It was found that only one factor, namely, “customers seeking novelty,” developed a constructive attitude toward counterfeit products. The other two – consumers seeking status, namely “with a sense of integrity,” and those who “perceived risks” in purchasing counterfeit goods developed a negative attitude toward the same. It was further found that formed attitudes, positive or negative, influenced customers’ willingness to buy counterfeit products. Practical Implications : Genuine brand manufacturers of handbags must target customers who are status-conscious and law-abiding when making a purchase. This could be done by running a campaign against counterfeit products and making prospective customers aware of the harmful effects of such purchases on the economy and society. Since it was found that individuals seeking new ideas might end up purchasing counterfeit products, marketers needed to attract these customers through other functional and non-functional aspects. Organizations should monitor both offline and online marketplaces to stay competitive. As the study found that integrity seemed to be a significant influencing factor in attitude formation and willingness to purchase counterfeit handbags, this could be achieved through the legal route. Originality : The current research is reliable, as it demonstrates a direct relationship between the factors underlying counterfeit purchases and customer attitude as well as the customer attitude and willingness to buy. However, no study has been carried out on counterfeit handbags.